1977
DOI: 10.1084/jem.145.3.607
|View full text |Cite
|
Sign up to set email alerts
|

Differences in pyrogen production by mononuclear phagocytes and by fibroblasts or HeLa cells.

Abstract: Phagocytosis of bacteria stimulates "professional" phagocytes to produce and release endogenous pyrogen (EP), the protein that mediates fever. To determine whether "nonprofessional" phagocytes also have this capacity, mouse and human fibroblasts and HeLa cells were cultured after ingestion of latex or chicken erythrocytes (CE), and EP release into culture supernate measured by mouse assay. No detectable pyrogen was released by these cell types after phagocytosis, whereas both latex and CE stimulated EP product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

1978
1978
2006
2006

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 26 publications
(36 reference statements)
2
10
0
Order By: Relevance
“…We have shown that incubation with S. albuis as a phagocytic stimulus induces the production of pyrogen by normal human, rabbit and mouse monionuclear phagocytes (3,15,16,20), and augments production by mouse macrophage tumor cell linies (19). Similar incubations with U-937 showed no effect on pyrogen levels (not shown), consistent with their verv low capacity for phagocytosis (9).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We have shown that incubation with S. albuis as a phagocytic stimulus induces the production of pyrogen by normal human, rabbit and mouse monionuclear phagocytes (3,15,16,20), and augments production by mouse macrophage tumor cell linies (19). Similar incubations with U-937 showed no effect on pyrogen levels (not shown), consistent with their verv low capacity for phagocytosis (9).…”
Section: Resultsmentioning
confidence: 99%
“…In all such cases, however, both host leukocytes and tumor cells have been present in the tissues, and no distinction could be made as to which cell type or types were responsible for the EP production. Recently, several mouse macrophage tumor cell lines were reported to release pyrogen during in vitro culture in pyrogen-free fetal bovine serum, whereas no pyrogen was detected in supernates from human fibroblasts, HeLa cells (16), hepatoma or renal cell carcinoma cell lines (19). Because it appears that of nonmalignant cells, only bone marrow-derived phagocytic cells have the capacity for normal pyrogen production and release after stimulation (16), we decided to study two macrophage-related tumor cell lines of human origin.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This explains the fever elicited by endotoxin and other microbial products [24]. It may also contribute to fever in various chronic inflammatory states.…”
Section: Secretion Of Endogenous Pyrogenmentioning
confidence: 99%
“…aZ., 1982;Amento et aZ., 1982a). Fibroblasts, L1210 cells, lymphoblasts, HeLa cells, baby hamster kidney, 3T3, and Vero ce11s are a11 reportedly incapable of IL-1 secretion (Root et aZ., 1970;Bodel and Miller, 1977;. The literature on endogenous pyrogen and LEM heavily references the production of IL-1 by neutrophils based upon an early experiment of Beeson (1948) showing that the PMN-rich peritoneal exudates of the rabbit produce pyrogen.…”
Section: Secreting Cellsmentioning
confidence: 99%